(untitled) (Research, Society and Development, 2020)
In this article we present results of the empirical research that aimed to study the understanding of teachers of Natural Sciences in elementary education had on evaluation, to answer the following question: what are the perceptions of teachers of natural science on evaluation and examination? We used the semi-structured interview as a data collection technique applied to six teachers from the matogrossense state network in elementary schools, in the urban region of Rondonópolis, Mato Grosso, Brazil. Data analysis was carried out through categorization during the process of critical-reflexive analysis of data from empirical research. The research data allowed us to verify of the six participating teachers, five perceived and practice the evaluation as examination, do not distinguish between both concepts and practices. That is, the predominant perception is to consider the examination as an evaluation that is due to two dominant factors: the examination is the predominant action in universities and schools, under the mask of “evaluation” (pseudo-evaluation) and; the absence of an evaluation study during teacher training. As examination is the determining practice during training, it is automatically transferred to school practices in basic education. Which refers to the need for a thorough curriculum and policy review of training programs and courses and teaching practices.